DETEKSI DEPRESI PADA SISWA BERBASIS WEB (STUDI KASUS: MTs TERPADU RAUDLATUL QUR’AN LAMONGAN) - Miftahus Sholihin; Dinar Mahdalena Leksana; Erna Hayati; Abdul Kholiq; M. Rosidi Zamroni; M. Khairul Anam; Akhmad Nurali Sulaiman; Moch. Zuhrul Umam; M. Miftah Fatkhul U; Diko Prastowo (Program Vokasi Universitas Negeri Gorontalo, 2024)
This Students' mental health in the school environment is becoming increasingly important. Depression, as a severe mental health disorder, can have a negative impact on students' well-being and academic achievement if it is not detected and treated appropriately and quickly. This service program aims to detect depression in MTs Roudlatul Qur'an students as early as possible to reduce the risk of ongoing depression. This can be done by building a website-based system that students can use to detect depression independently. This system was created to make it easier for students to recognize the early symptoms of depression by selecting the symptoms according to what they are experiencing. With this system, it is hoped that it can prevent depression as early as possible for students and teachers quickly and more efficiently, thereby reducing students who are at risk of experiencing depression. Apart from that, the system provides valuable information for students and teachers to understand depression more deeply and find ways to overcome it. Through this program, it is hoped that awareness of the importance of mental health in the school environment can increase and create a healthier and more supportive learning environment for all students.